Immune surveillance reactivation to improve overall survival in small cell lung cancer (SCLC): The randomized IMPULSE study - Thomas, Michael (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: The immune surveillance reactivator lefitolimod (MGN1703), a DNA-based Toll-like receptor 9 (TLR9) agonist, was compared to placebo in metastatic CRC (mCRC) patients with disease control after standard induction chemotherapy in the double-blind randomized phase 2 IMPACT study. Lefitolimod showed a superior effect over placebo in exploratory analyses of pretreatment characteristics that identified patients most likely to benefit from lefitolimod. A study in small cell lung cancer (SCLC) patients, IMPULSE, was designed to confirm this preliminary evidence of efficacy in a new, high-mortality-and-unmet-need indication.Trial design: Trial characteristics: IMPULSE is a randomized, international, multicenter, open-label trial to assess the effect of TLR9-mediated immune surveillance reactivation on overall survival (OS) in extensive-disease (ED) SCLC patients. Secondary endpoints include PFS, response rates, safety, and quality of...
Gesehen am 15.11.2017